2023
DOI: 10.1155/2023/5827613
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in Rat Lung Tissue during Severe Acute Pancreatitis-Associated Acute Lung Injury: Protection of Qingyi Decoction

Abstract: Qingyi decoction (QYD) has anti-inflammatory pharmacological properties and substantial therapeutic benefits on severe acute pancreatitis (SAP) in clinical practice. However, its protective mechanism against SAP-associated acute lung injury (ALI) remains unclear. In this study, we screened the active ingredients of QYD from the perspective of network pharmacology to identify its core targets and signaling pathways against SAP-associated ALI. Rescue experiments were used to determine the relationship between QY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…QYD is a TCM commonly used after surgery for the treatment of SAP. In previous studies, our team has shown the potential for QYD to treat SAP-ALI or SAP-related multiple organ dysfunction by exerting antiinflammatory and enhancing the intestinal barrier while simultaneously maintaining immune homeostasis ( 47 , 48 ). Furthermore, QYD has been shown to mediate the recovery of intestinal dysbiosis in SAP, indicating its role in regulating intestinal bacteria ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…QYD is a TCM commonly used after surgery for the treatment of SAP. In previous studies, our team has shown the potential for QYD to treat SAP-ALI or SAP-related multiple organ dysfunction by exerting antiinflammatory and enhancing the intestinal barrier while simultaneously maintaining immune homeostasis ( 47 , 48 ). Furthermore, QYD has been shown to mediate the recovery of intestinal dysbiosis in SAP, indicating its role in regulating intestinal bacteria ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“… 11–15 Moreover, it is not only limited to pancreatic injury in AP but is also involved in the kidney injury and lung injury caused by AP. 16–18 These findings emphasize the important role of ferroptosis in the AP process. Ultimately, it was found that ferroptosis and AP are closely associated and jointly affect the AP disease process in several ways.…”
Section: Introductionmentioning
confidence: 82%
“…This suggests that QYD has potential therapeutic efficacy in treating lung injury related to severe acute pancreatitis (SAP). Originating from the formula in "Shanghan Lun," as a decoction made from Chinese herbal medicine, QYD is employed in the treatment of acute pancreatitis (AP) patients due to its laxative, heat-clearing, and detoxifying properties [134,135]. Uncoupling Protein-2 (UCP2) is crucial for managing ROS, maintaining redox balance, and modulating immune responses.…”
Section: Acute Lung Injurymentioning
confidence: 99%